Calcite Precipitation In Bio-Mediated Tropical Residual Soil - Yee, Jason (2020)
Biomediation in soil for improvement is a relatively new approach and environment friendly method in civil engineering. This method induces calcium carbonate (calcite) through the biological process of microbes which known as Microbial Induced Calcite Precipitate (MICP). There are less studies on the evaluation of biomediation in fine-grained soil such as clay in tropical residual soil, so far fine sands were used as the primary material for the research of MICP treatment. This purpose of this project is to study the effect of reagent concentrations on strength properties and calcite content of biomediated tropical residual soil as well as the uniformity of calcite precipitation. 3 sets of soil specimens were prepared by well mixing 1 x 108 cfu/ml of urease-forming bacteria, Sporosarcina Pasteurii with the tropical residual soil.